Dinâmica de perda de P durante eventos de chuva-vazão na bacia hidrográfica de Arvorezinha - Bender, Marcos Antônio (2016)
In recent years, the intensification of agricultural activities has led to a widespread increase in phosphorus in surface waters causing environmental, social and economic problems due to eutrophication. The objective of this paper is to describe the loss dynamics of P during events of rain flow in the hydrographic basin of Arvorezinha. The study was carried out in the hydrographic basin of the Lajeado Ferreira stream, municipality of Arvorezinha, RS (28 52’S e 52 05’O), with 1,19 km2 of area. Nine events were analyzed (116 samples) during the period of July 2011 to July 2015. The pH and electrical conductivity were measured immediately after the arrival of the samples in the laboratory. An aliquot of water+sediment sample was filtered at 0,22 μm. In the filtrate, the cations were determined by atomic emission spectrometry by Inductively Coupled Plasma (ICP-OES), and the concentration by high performance ion (liquid) chromatography (HPLC). The total content of P of the water+sediment samples were determined in ICP-OES after acid digestion (HCl + HNO3) assisted by microwave oven. In the mouth of the basin, the flow was monitored by reading the water levels on a linigraph installed on a Parshall flume and the sediment concentration in suspension (CSS) was estimated by the correlation between measured CSS and turbidity. The precipitation was monitored with rain gauges and pluviographs installed in the basin. In order to estimate the chemical speciation of the ions in solution the program Visual Minteq (for Windows) version 3.1 was used. For the interpretation of the dissolved P hysteresis, a 3-component model was used. Due to the high affinity of the soils for P most of the nutrient was lost in the particulate form (88%), however, in a reduced environment part of this P can be desorbed and become bioavailable. Since the largest losses of P occur during the events, the seasonal samplings underestimate the real trophic state of the waters being necessary its inclusion to know the dynamics of transference. The majority of the dissolved P is in the free form ranging from 89 to 99% of the total mass of dissolved P. The pH was the main characteristic that altered the distribution of the dissolved species of P. The runoff of surface and subsurface water was responsible for most of the transport of dissolved P. A good correlation between the contents of CSS and total and particulate P was found. The total P content exceeded the limit allowed by CONAMA's resolution in almost all events. For the collected events, there was a predominance of sediment peaks and total P preceding the peak flow. The hysteresis index fell in the end of the winter and in early spring, since the soil was mobilized increased the amount of sediment and P available increasing their contribution to the fluvial channel.